A New Genus of Macropsinae (Hemiptera: Cicadellidae) From Madagascar. Issue 1 (7th July 2016) - Yang, Liyuan; Dietrich, C.H.; Zhang, Yalin
Abstract: Paragalboa acuta gen. & sp. n. is described and illustrated from Madagascar. The new genus shows morphological affinities to the Macropsini genus Galboa Distant recorded from Seychelles. A checklist of all known genera of Macropsinae is provided.